Apakah IPA Membosankan? Self-Efficacy dan Pemahaman Sains Mahasiswa PGSD - Edy Mawardi; Wahyu Kurniawati; Ikhlasul Ardi Nugroho; Supartinah (Postgraduate, University of Mataram, 2025)
This study aims to examine the correlation between PGSD students' perception (X) of self-efficacy (Y1) and understanding of science (Y2). The problem with this study arises because it is not clear whether students' perception of science learning has an effect on their self-efficacy and conceptual understanding, even though their average comprehension score is quite good (Mean = 71.19). This study uses a correlational quantitative approach involving 21 PGSD UPY students. Perceptions were measured using a questionnaire that had been tested for reliability (α = 0.712), Self-efficacy is measured with its own instruments (α = 0.740), meanwhile, scientific understanding is measured through tests validated through the validity of the content by experts. Data normality test (Shapiro-Wilk, p > 0.05) indicates the data is normally distributed, so Pearson correlation analysis is used. The results showed a significant positive correlation between perception and self-efficacy (r = 0.827; p < 0.01), however, no significant relationship was found between perception and understanding of science (0.297), and between self-efficacy and understanding of science (0.220). These findings indicate that students' positive perceptions are related to self-efficacy, but do not directly affect the conceptual understanding of science.